Edukasi pengelolaan Dismenore pada remaja putri di Pondok Pesantren Rofiatul Islam - Narsih, Umi; Shofia, Vivi; Sulistyorini, Endah; Damayanti, Eva Alfina (P3HKI - Universitas Muhammadiyah Parepare, 2024)
Adolescence is a transitional period characterized by physical, psychological, and biological changes, including menstruation, which may be accompanied by dysmenorrhea, a condition that causes abdominal pain and can affect daily activities. Knowledge about dysmenorrhea management among adolescent girls is often inadequate, especially in Islamic boarding schools. due to limited access to quality healthcare services, such as medical examinations, appropriate treatment, and timely care. This community service program aimed to enhance adolescent girls' knowledge of dysmenorrhea management and improve their quality of life by reducing the impact of menstrual pain. The program was conducted at Rofiatul Islam Islamic Boarding School in Sentong Village, Krejengan District. Activities included pre-test and post-test questionnaires, distribution of educational leaflets, and counseling sessions focusing on the causes of dysmenorrhea, risk factors, and management techniques. Data analysis was performed by comparing pre-test and post-test results to evaluate the improvement in participants' knowledge. A total of thirty participants took part in this program. The pre-test results showed that 73% of participants had good knowledge, while 27% had moderate knowledge. After the education and counseling sessions, the post-test results indicated an improvement, with 93% of participants demonstrating good knowledge and 7% showing moderate knowledge, signifying a significant increase in understanding. This program successfully enhanced participants' comprehension of dysmenorrhea and its management. Further education on this topic is recommended to increase awareness and encourage its practical application in daily life.